Chaotic thermalization in classical gauge theories - Woitek, Marcio [UNESP]; Krein, Gastão [UNESP] (AIP Publishing, 2013)
We explore the idea that chaos concepts might be useful for understanding the thermalization in gauge theories. The SU(2) Higgs model is discussed as a prototype of system with gauge fields coupled to matter fields. Through the numerical solution of the equations of motion, we are able to characterize chaotic behavior via the corresponding Lyapunov exponent. Then it is demonstrated that the system's approach to equilibrium can be understood through direct application of the principles of Statistical Mechanics. © 2013 AIP Publishing LLC.
Keywords: Chaos; Gauge Theories; Thermalization